Income convergence or divergence? Study on selected Muslim countries - Duasa, Jarita (IIUM Press, 2009)
In this study, the existence of income convergence or income divergence is investigated on ten selected OIC (the Organisation Islamic Conference) economies. The results are then linked to the degree of openness in which the countries use globalization indices. In order to investigate the existence of either income convergence or divergence between selected Islamic countries, income differentials between selected OIC countries and the benchmark country are computed and a series of test is done. The test include stationary linearity test using Augmented Dickey-Fuller (ADF) test for linear time-series and non-linear stationary test using Kapetanious et al (KSS). The findings are that most of the countries experience income divergence except for three countries. By analyzing the degree of globalization in these economies, it is found that the results support the endogeneous theory and depending approach which predict that globalization is likely to cause income divergence (inequality) rather than convergence (quality)